Analisis Prosedur Pengamanan Kargo dan Pos di Regulated Agent YIA - Syifa Fauziah; Jefri Irawan Purnomo (PT FORMOSA CENDEKIA GLOBAL, 2022)
The national and international regulations set out to control the transport of cargo by air is the statement of the 2017 prime minister of transportation (international civil aviation organization) in a few annex, and yet there are still several incidents of contraband that escaped inspection and ended up in the air, as this text aims to study the factors that led up to it. The writer used a qualitative method in the study, with a descriptive qualitative data in which the data expressed in the form of statements or words that describe the good work of circumstances, processes, events and other events during research in the field. The researcher concluded that in the implementation of cargo security of cargo has been done well by regulated agents as the cargo examination department and has been implemented according to applicable rules. Researchers found another factor that became a regulated agent staff constraint in conducting cargo checks, namely the delay of goods that came to the regulated agent this is due to the sender who did not ship the goods to the agent (EMPU) on time so that the agent also late submitting goods to RA.